Analisis Pengembangan Usaha Mebel Dengan Metode SWOT: Studi Kasus Pada Usaha Mebel Berkah Mandiri Desa Padang Mekar Kecamatan Padangguni Kabupaten Konawe - Leni Saleh; Riana Nur Fadilla; Novita Ramadani; Nuryanti Nuryanti; Juli Eka Putri; Desi Rianti; N. Rias; Imel Setiana Tagu; Rian Andika Putra; Nasmuddin Nasmuddin; Tiwal Tiwal (Journal of Student Research, 2024)
The purpose of this study was to determine the development strategy of Berkah Mandiri furniture business using the SWOT method. The study was conducted at Berkah Mandiri Furniture Business owned by Mr. Watiman in Padang Mekar Village, Padangguni District. The respondents were the owners of the Berkah Mandiri Furniture industry. The analysis method used in this study was SWOT analysis. SWOT analysis is used to create a strategy in developing the Berkah Mandiri Furniture business. The results of the IFAS and EFAS analysis conducted on the Berkah Mandiri Furniture business development strategy in Padang Mekar Village, Padangguni District, showed that the current state of the Berkah Mandiri Furniture business is in a favorable situation (quadrant 1). The strategy that must be implemented in this condition is to support an aggressive growth policy (Growth oriented strategy) to increase income. Keywords: